Analisis Trend Solvabilitas, Profitabilitas, Dan Likuiditas Dalam Mengevaluasi Laporan Keuangan (Studi Kasus PT. Adaro Energy. Tbk Periode 2018-2021 ): Studi Kasus PT. Adaro Energy. Tbk Periode 2018-2021 - Bambang Widjanarko Susilo; Febryantahanuji Febryantahanuji (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to evaluate how the trend of PT Adaro Energy Tbk's financial performance in terms of solvency, profitability, and liquidity. To measure financial performance, PT Adaro Energy Tbk's financial statements from 2017 to 2019 are used as sources, and the ratios used are solvency, profitability, and liquidity ratios. The study found that over the past three years, the company's profitability ratio has shown a downward trend. This is indicated by the decrease in GPM (Gross Profit Margin), OPM (Operating Profit Margin), NPM (Net Profit Margin), ROA (Return on Assets), ROE (Return on Equity), and liquidity ratio, as indicated by the decrease in the CR (Current Ratio) proxy ratio. Only the financial solvency ratio shows the progress indicated by the declining solvency rate of the proxies.